2014
DOI: 10.1111/cpf.12202
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of health‐related physical fitness tests in adolescents: the MOVE Program

Abstract: The aim was to examine the reliability of health-related physical fitness tests that were used in a French health promotion program 'Move…A priority for your health'. Participants were 174 French youth (88 children and 86 adolescents) aged 8·2-16·2 years. Aerobic fitness, muscular strength, speed and flexibility were tested using 20-m shuttle run test, ½ mile run test, basketball throw, standing long jump, shoulder stretch and 20/30/50-m sprint tests. Reliability was calculated for the basketball throw, standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
(58 reference statements)
4
28
1
6
Order By: Relevance
“…The 20 m run, for the overall sample and boys, and the 40 m run, for girls, were the only tests where significant differences were found between test–retest values. These results differ from those of previous studies conducted in the general population, where the 20 m and 40 m run tests were found to be reliable (Castro‐Pinero et al, 2010; Vanhelst et al, 2016). Notwithstanding, the 20 m and 40 m run tests presented good or excellent ICC values and strong to the almost perfect agreement in our sample of young athletes, with exception for the 20 m speed run in girls that presented moderate reliability (ICC = 0.57).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The 20 m run, for the overall sample and boys, and the 40 m run, for girls, were the only tests where significant differences were found between test–retest values. These results differ from those of previous studies conducted in the general population, where the 20 m and 40 m run tests were found to be reliable (Castro‐Pinero et al, 2010; Vanhelst et al, 2016). Notwithstanding, the 20 m and 40 m run tests presented good or excellent ICC values and strong to the almost perfect agreement in our sample of young athletes, with exception for the 20 m speed run in girls that presented moderate reliability (ICC = 0.57).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, information on physical fitness fosters knowledge on understanding the physiologic development of youth (Brown, Patel, & Darmawan, 2017), while supporting the identification and development of athletic talents. Generally, physical fitness is assessed using a combination of tests aimed at analysing specific physiological components, such as anthropometric measures (e.g., height, weight, waist circumference), cardiorespiratory fitness (CRF), upper and lower muscular fitness (MF), and agility and speed (Ortega, Ruiz, & Castillo, 2008; Vanhelst, Beghin, & Fardy, 2016). The physical fitness monitoring of adults athlete populations is well established, while in young athletes it is scarce (Armstrong & Barker, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful examples are the Assessing Levels of Physical Activity study (ALPHA study) [8], which aimed to identify reliable fitness tests for children and adolescents; the AVENA study, which aimed to evaluate cardiovascular fitness in youth around Europe [9]; the Healthy Lifestyle in Europe by Nutrition in Adolescence study (the HELENA study) [10], which evaluated physical fitness over 10 European nations; FitnessGram [11], whose purpose was to increase the levels of physical activity in children in the United States; and EUROFIT [12], a program in Europe. All these attempts firstly detected the reliability of the fitness tests for specific populations and secondly provided age-related fitness percentile values [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The result of the test is either a successful "1" or unsuccessful "0" contact. According to Vanhelst et al (2014) the test shows high reliability (r = 0.91) in children and youth.…”
Section: Measurementsmentioning
confidence: 99%